Current misjudgments and future trends in rehabilitation after knee injuries (Part 1) - Freiwald, J.; Hoppe, M. W.; Javanmardi, S.; Hotfiel, T.; Engelhardt, M.; Grim, C.; Baumgart, C. (Sport-Orthopädie - Sport-Traumatologie, 2020)
For many years, strength training has been an integral part of rehabilitation after knee trauma. In the first part of the paper, new research results on muscle contraction, especially eccentric muscle action, are presented in rehabilitative accentuated strength training after knee trauma. It is pointed out that the strength training methodology, which has mostly been validated with young and athletic persons, cannot be transferred to persons with knee traumas. Biomechanical stress during rehabilitative, every day, and sports activities will be discussed as well as the additional joint stress caused by activated muscles and various co-factors. In the second part of the paper, the theoretical considerations are illustrated using selected examples of strength training after knee trauma, and an outlook on future strategies is given.